Accelerated innervation of biofabricated skeletal muscle implants containing a neurotrophic factor delivery system - Mashanov, Vladimir; Billman, Erika; Poerio, Aurelia; Kaufmann, Mary; Lai, Dehui; Vaughan, J. William; Kim, Ickhee; Ju, Young Min; Atala, Anthony; Yoo, James J.; Kim, Ji Hyun (Frontiers in Bioengineering and Biotechnology, 2024)
Volumetric muscle loss (VML) is one of the most severe and debilitating conditions in orthopedic and regenerative medicine. Current treatment modalities often fail to restore the normal structure and function of the damaged skeletal muscle. Bioengineered tissue constructs using the patient's own cells have emerged as a promising alternative treatment option, showing positive outcomes in fostering new muscle tissue formation. However, achieving timely and proper innervation of the implanted muscle constructs remains a significant challenge. In this study, we present a clinically relevant strategy aimed at enhancing and sustaining the natural regenerative response of peripheral nerves to accelerate the innervation of biofabricated skeletal muscle implants.We previously developed a controlled-release neurotrophic factor delivery system using poly (lactic-co-glycolic acid) (PLGA) microspheres encapsulating ciliary neurotrophic factor (CNTF) and glial cell line-derived neurotrophic factor (GDNF). Here, we incorporate this neurotrophic factor delivery system into bioprinted muscle constructs to facilitate innervation in vivo. Our results demonstrate that the neurotrophic factors released from the microspheres provide a chemical cue, significantly enhancing the neurite sprouting and functional innervation of the muscle cells in the biofabricated muscle construct within 12 weeks post-implantation. Our approach provides a clinically applicable treatment option for VML through accelerated innervation of biomanufactured muscle implants and subsequent improvements in functionality.